Outcomes of trimodality CROSS regimen in older adults with locally advanced esophageal cancer. Issue 10 (October 2021) - Cooper, Lisa; Dezube, Aaron R.; De León, Luis E.; Kucukak, Suden; Mazzola, Emanuele; Dumontier, Clark; Mamon, Harvey; Enzinger, Peter; Jaklitsch, Michael T.; Frain, Laura N.; Wee, Jon O.
Abstract: Background: Chemoradiotherapy for Esophageal cancer followed by Surgery (CROSS regimen) is standard of care for locally-advanced esophageal cancer. We evaluated CROSS completion rates, toxicity, and postoperative outcomes between older and younger adults receiving trimodality therapy. Methods: Retrospective analysis of patients with locally-advanced esophageal cancer who underwent CROSS regimen from May 2016 to January 2020 at a single academic center. Outcomes of those aged ≥70-years-old and <70 years-old were analyzed. Results: Of 201 patients, 136 were <70 and 65 were ≥70 years. Older adults were more likely to be male (91% vs. 79%; p = 0.045), have higher ECOG scores (median 1 vs. 0; p = 0.003), Charlson-comorbidity index (median 6 vs. 4; p < 0.001), and undergo open procedures (20% vs. 8% p = 0.008). Most completed CROSS regimen (78% vs. 84% respectively) with similar rates of treatment discontinuation and dose reduction (all p > 0.05). Time to surgery following neoadjuvant therapy was similar between age groups, except in those ≥80-years-old as compared to <70-years-old (p < 0.05). Overall toxicity rates were similar (68% vs. 71% respectively; p = 0.676). Only rates of delirium (19% vs. 5%) and urinary retention (9% vs. 0%) were higher in older adults (both p < 0.05). Length of stay, discharge disposition, mortality, and overall survival were similar. Age was not an independent risk factor for complication, neoadjuvant toxicity or completion, surgery timing, nor worse overall or recurrence-free survival (p > 0.05). Conclusion: Trimodality CROSS regimen for esophageal cancer in older adults is feasible, with similar completion rates and postoperative outcomes as compared to their younger counterparts.